The Influence of Teacher Professionalism on Students Motivation to Learn Arabic at M.A Alkhairaat Gorontalo City - Suronoto, Siti Nur Muthiah; Damhuri, Damhuri; Bt. H. Bahri, Ratni (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This study aims to determine the relationship between Arabic language teacher professionalism and Arabic language learning motivation of class X and class XI students at Madrasah Aliyah Alkhairaat Gorontalo City. The method used in this research is non-experimental quantitative method by using questionnaire, interview, documentation and observation data collection techniques. The results of this study indicate that professional teachers can affect student learning motivation. Conversely, if the teacher is not competent, then students will be reluctant to learn because it is not balanced with learning motivation. Although teacher professionalism has a big role, without the encouragement or great desire from within students, students are not so eager to participate in learning so that the learning outcomes obtained will be less satisfying. However, student success in achieving achievement is not only determined by teacher professionalism and learning motivation alone, but there are still many internal or external factors that can affect the learning outcomes of each student.